Therapy selection for tinea corporis and cruris with commorbidity: 3 case series - Yefta, Yefta; Winarni, Dwi Retno Adi; Siswati, Agnes Sri (Journal of General - Procedural Dermatology and Venereology Indonesia, 2023)
Background: Dermatophytosis is a superficial (skin, hair and nails) fungal infection caused by dermatophyte group fungi (Trichophyton, Epidermophyton and Microsporum). Immunocompromised conditions cause fungal infections to become more widespread and require consideration of therapy. Case Illustration: This case series represented three cases of tinea corporis and tinea cruris in patients with comorbidities. The first case was tinea corporis and tinea cruris in a patient with congestive heart failure with oral terbinafine therapy. The second case was tinea corporis and tinea cruris in a patient with bilateral fourth degree hydronephrosis with oral griseofulvin therapy. The third case was tinea corporis in a patient with autoimmune hemolytic anemia with oral itraconazole therapy. A two-week post-systemic antifungal evaluation gave good results in all of the patients. Discussion: Selection of antifungals in dermatophytosis cases considering the patient's condition (contraindications and side effects that can be caused) provides a good outcome in patients with comorbidities. Conclusion: Dermatophytosis (tinea corporis and tinea cruris) is common in immunocompromised patients. This is due to decreased immunity causing dermatophytes to develop easily on the skin. Selection of the right therapy, considering comorbid conditions is important in order to get the best results for the patients.